IMPLEMENTATION OF ARCHIPELAGO INSIGHTS IN NATIONAL INTEGRATION - Andika Ronggo Gumuruh; Tofan Priananda Adinata (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
The existence and prestorika glosnot that struck Eastern Europe result in Unisoviet countries and Yogoslovakia disintegrating. Events over a significant impact on the Unitary Republic of Indonesia (NKRI), the regions fery-fery (penggiran) began to flare, the suburbs have aspirations for independence such as East Timor is now independent, the Free Aceh Movement (GAM), Papua Organization Merdeka (OPM), the South Maluku Republic (RMS). The seeds of disintegration of the more fertile when Suharto's authoritarian government with a military approach to evaluate policy without political borders to prosper his people. The existence of globalization, trade liberalization, and strengthening of new ethnicities (awareness of the rights of tribal nationalities) increasingly stronger demands of the suburbs of his rights to ask whether social, political and economic welfare to accelerate. The factors and conditions above lead-freksi freksi and regional upheaval that gave birth to the potential for violence and bloody conflict. This is due to the absence of a shared perception among citizens. Archipelago is the answer to the same perception to live together in the corridor (the Republic of Indonesia) NKRI and realizing national integration